PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONPADA MATERI LINGKARAN(Eksperimentasi Pada Siswa Kelas VIII SMP Negeri 1 Tondano) - Millenika Putri Purba; Anetha L.F Tilaar; Marvel G. Maukar (CV. ADIBA AISHA AMIRA, 2023)
Based on the results of observations and interviews that have been conducted at SMP Negeri 1 Tondano, information was obtained that the learning process is still using the direct learning model. Where learning is only centered on the teacher, so students are less active in learning mathematics.This causes students to have grades that are standard or below average. This cen be seen from the average score of students, which is 67.5, while the Minimum Completeness Criteria (KKM) set in schools is 75. The purpose of this study is to determine whether the learning outcomes of students who use the cooperative learning model of the student teams achievement division type are higher from student learning outcomes using direct learning models on circle material. The experimental design used in this study was a posstest control group design. the sample of this study was class VIIIC as the experimental class with 28 students and class VIIIB as the control class with 29 students at SMP Negeri 1 Tondano. Data obtained from student learning outcomes tests. With the average student learning outcomes in the experimental class was 81.64 and the average student learning outcomes in the control class was 72.85. analysis of the data using the t-test with a value of ???????????????????????? = 1.902 > ???????????????????????? = 1,67 then reject ????0 and accept ????1. The results of the study concluded that student learning outcomes taught by cooperative learning model type student teams achievement division were higher than student learning outcomes taught using direct learning models, so that they were well applied to the process of learning activities.